Analisis Kemampuan Motorik Halus Melalui Kegaitan Bermain Balok di Raudatul Atfal (RA) Miftahul Huda Waringinsari Kota Banjar - Siti Munawaroh; Naeli Mutmainah (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2022)
The purpose of this study was to describe whether block games can improve the fine motor skills of children in Raudatul Atfal (RA) Miftahul Huda Waringinsari Banjar City. The method in this research is using the Field Research method where researchers go directly to the field to uncover and explore the block game used by teachers to improve fine motor skills in early childhood. The results showed that with 1) good cooperation and preparation between children and teachers when learning activities to play blocks and 2) forming simple shapes, 3) forming shapes rather difficult, 4) being skilled at forming blocks can increase creativity, so this is a child -The children of RA Miftahul Huda Waringinsari experienced an increase in the good category in listening to explanations about the method of playing blocks.